Advanced X‐ray imaging at beamline 07 of the SAGA Light Source. (21st October 2021) - Yoneyama, Akio; Takeya, Satoshi; Lwin, Thet Thet; Takamatsu, Daiko; Baba, Rika; Konishi, Kumiko; Fujita, Ryusei; Kobayashi, Keisuke; Shima, Akio; Kawamoto, Masahide; Setoyama, Hiroyuki; Ishiji, Kotaro; et al.
Abstract : The paper describes the new X‐ray imaging resources, including micro‐computed tomography (CT), phase‐contrast CT, low‐temperature CT and time‐resolved topography, that are available at beamline 07 of the SAGA Light Source. Abstract : The SAGA Light Source provides X‐ray imaging resources based on high‐intensity synchrotron radiation (SR) emitted from the superconducting wiggler at beamline 07 (BL07). By combining quasi‐monochromatic SR obtained by the newly installed water‐cooled metal filter and monochromatic SR selected by a Ge double‐crystal monochromator (DCM) with high‐resolution lens‐coupled X‐ray imagers, fast and low‐dose micro‐computed tomography (CT), fast phase‐contrast CT using grating‐based X‐ray interferometry, and 2D micro‐X‐ray absorption fine structure analysis can be performed. In addition, by combining monochromatic SR obtained by a Si DCM with large‐area fiber‐coupled X‐ray imagers, high‐sensitivity phase‐contrast CT using crystal‐based X‐ray interferometry can be performed. Low‐temperature CT can be performed using the newly installed cryogenic system, and time‐resolved analysis of the crystallinity of semiconductor devices in operation can be performed using a time‐resolved topography system. The details of each instrument and imaging method, together with exemplary measurements, are presented.